Animal and Human Brucellosis in Pakistan - Jamil, Tariq; Khan, Aman Ullah; Saqib, Muhammad; Hussain, Muhammad Hammad; Melzer, Falk; Rehman, Abdul; Shabbir, Muhammad Zubair; Khan, Mumtaz Ali; Ali, Shahzad; Shahzad, Asim; Khan, Iahtasham; Iqbal, Mudassar; et al. (Frontiers in Public Health, 2021)
Brucellosis is a bacterial zoonotic disease that affects different animal species and can be spread to humans via direct contact as well as via the food chain. Although brucellosis is a serious health hazard, its significance has largely been neglected in many countries. However, brucellosis has been the subject of interest in developing countries, especially in Pakistan where this disease is endemic. Brucellosis is a puzzling disease in terms of taxonomy and typing, clinical signs, pathobiology, diagnosis, vaccination and treatment. Practical eradication programs include test and slaughter policies and vaccination as preventive measures in animals. The purpose of this review was to provide an updated and comprehensive insight into brucellosis in Pakistan with particular emphasis on its occurrence in humans and various animal species, the diagnostic tests applied as well as prevention, treatment and eradication aspects.